The Summer Drop in Female Employment - Brendan M. Price; Melanie Wasserman (Center for Economic Studies and ifo Institute (CESifo), 2022)
We provide the first systematic account of summer declines in women's labor market activity. From May to July, the employment-to-population ratio among prime-age US women declines by 1.1 percentage points, whereas male employment rises; women's total hours worked fall by 11 percent, twice the decline among men. School closures for summer break-and corresponding lapses in implicit childcare-provide a unifying explanation for these patterns. The summer drop in female employment aligns with cross-state differences in the timing of school closures, is concentrated among mothers with young school-age children, and coincides with increased time spent engaging in childcare. Decomposing the gender gap in summer work interruptions across job types defined by sector and occupation, we find large contributions from both gender differences in job allocation and gender differences within jobs in the propensity to exit employment over the summer. Summer childcare constraints may contribute to gender gaps in career choice and earnings: women-particularly those with young school-age children-disproportionately work in the education sector, which offers greater summer flexibility but lower compensation relative to comparable jobs outside of education.
Keywords: J13; J16; J22; J24; 330; gender gap; seasonality; labor force participation; childcare; time use; school closure